FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN DEVISA DAN NET EKSPOR DI INDONESIA - Febriyenti, Mega; Aimon, Hasdi; Azhar, Zul (Jurnal Kajian Ekonomi, 2013)
This study aims to analyze and determine (1) the influence of net exports, foreign debt, FDI, and foreign reserves previously period against reserves in Indonesia. (2) the influence of the economy, the economy and the foreign exchange rate on net exports in Indonesia. This study using a simultaneous equations model analysis with Indirect Least Squared method (ILS) from the first quarter of 2000 - the fourth quarter of 2011. The research concludes that (1) Net exports, external debt and international reserves prior period reserves in Indonesia affected significantly. While the FDI variable does not affect reserves in Indonesia are significantly (2) Indonesia's economy, the Japanese economy and the exchange rate significantly affects net exports in Indonesia. Based on these results the policies recommended to the government of which the export should be developed by the excess exports over imports would benefit the government by increasing foreign exchange reserves, the need to foster a harmonious working relationship with trading partners, the need for trade policy strategy, especially in partner mediversifikasi major trading for export. Keyword : Foreign Reserves, Net Exports, Foreign Debt, FDI, Indonesia's economy, Japan's economy, Exchange